Correlation of Estradiol Concentration and Body Mass Index in Progestin Contraceptive User - Ari Susanti; Eryati Darwin; Rauza Sukma Rita (JURNAL PROTEKSI KESEHATAN, 2023)
One method of contraception that has high effectiveness is progestin contraception. One type of progestin, namely depot medroxyprogesterone acetate, can stimulate the appetite control center in the hypothalamus, causing an increase in appetite and body weight. The number that becomes the standard assessment to determine whether a body weight is classified as normal, underweight, overweight, or obese is the body mass index (BMI). This research aims to identify the relationship between estradiol levels and body mass index. This type of research is analytic. The research sample was 45 DMPA user. Data analysis used discriminant analysis. The results showed that estradiol levels of 56.4 ± 19.3 pg/mL tended to have normal BMI. Estradiol levels of 73.3 ± 47.7 pg/mL tend to be overweight. It can be concluded that there is no relationship between estradiol levels and body mass index.